2003
DOI: 10.1063/1.1615833
|View full text |Cite
|
Sign up to set email alerts
|

Technique for writing of nonlinear optical single-crystal lines in glass

Abstract: The technique for the writing of crystal lines in glass by Nd:YAG laser irradiation, selective atom heat processing, is applied to rare-earth (Sm3+, Dy3+) barium borate glasses, and nonlinear optical β-BaB2O4 (β-BBO) crystal lines with a width of ∼5 μm are fabricated. The crystal lines show uniform colors in polarized optical microscope and second-harmonic generation (SHG) measurements. The azimuthal dependence of SHG signals in the crystal lines is the same as that in commercially available β-BBO bulk single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 13 publications
5
99
0
Order By: Relevance
“…The effective second-order nonlinear optical coefficient, deff, is given by the equation of deff = d22cos 2 θ. It was confirmed that the SH intensity for the straight line shown in Figure 1 changes as a function of cos 2 θ, indicating that β-BBO crystals in the straight line are highly oriented and grow with the c-axis orientation along the laser scanning direction (e.g., Honma et al, 2003;Ogawa et al, 2013). The c-axis orientation of β-BBO crystals has been already proposed in the previous papers (e.g., Honma et al, 2003;Ogawa et al, 2013).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The effective second-order nonlinear optical coefficient, deff, is given by the equation of deff = d22cos 2 θ. It was confirmed that the SH intensity for the straight line shown in Figure 1 changes as a function of cos 2 θ, indicating that β-BBO crystals in the straight line are highly oriented and grow with the c-axis orientation along the laser scanning direction (e.g., Honma et al, 2003;Ogawa et al, 2013). The c-axis orientation of β-BBO crystals has been already proposed in the previous papers (e.g., Honma et al, 2003;Ogawa et al, 2013).…”
Section: Resultssupporting
confidence: 62%
“…In this work, crossing lines of nonlinear optical β-BaB2O4 (β-BBO) crystal were patterned by laser irradiation in Sm2O3-BaO-B2O3 glasses, and nucleation and crystal growth behaviors at the crossing point were examined from polarized optical microscope (POM) observations. So far, the patterning of highly oriented crystal lines (not crossing lines) of β-BBO in some glasses has been realized (Honma et al, 2003;Suzuki et al, 2012Suzuki et al, , 2013Ogawa et al, 2013;Nishii et al, 2015), and thus, β-BBO crystal would be a good example for the study of nucleation and crystal growth in the laser-induced crystallization in glasses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, crystal dots and lines consisting of nonlinear optical crystals such as b-BaB 2 O 4 , Ba 2 TiGe 2 O 8 , and (Sr,Ba)Nb 2 O 6 have been patterned on the glass surface by irradiations of lasers such as continuous wave (cw) Nd:YAG lasers with a wavelength of l = 1064 nm [6][7][8][9][10][11][12][13]. In those laser-induced crystallization techniques, irradiated lasers are absorbed by rare-earth (RE) ions such as Sm 3+ through f-f transitions or transition metal (TM) ions such as Cu 2+ through d-d transitions in glasses, and the laser energy absorbed by RE or TM ions is transferred to lattice vibrations through a non-radiative relaxation process (electron-phonon couplings).…”
Section: Introductionmentioning
confidence: 99%
“…Using REAH processing, we examined the patterning of crystalline dots or lines in various glasses. Especially, we reported the formation of single crystal lines consisting of nonlinear optical BiBO3 26) and β -BaB2O4 (β -BBO) 30) crystals in Sm2O3-Bi2O3-B2O3 and Sm2O3(Dy2O3)-BaO-B2O3 glasses. Furthermore, Ihara et al 29) have reported the writing of two-dimensional crystal curved or bending lines consisting of rare-earth ion doped BiBO3 crystals showing a second harmonic generation (SHG).…”
Section: Mechanism Of Laser-induced Local Heatingmentioning
confidence: 99%